Kebijakan Peraturan OJK Terhadap Perbankan Syariah dalam Menghadapi Wabah Covid-19 di Era New Normal - Fauzi, Inna; Anjani, Yassirlana (TAWAZUN: Journal of Sharia Economic Law, 2021)
This study aims to examine the policy of Islamic banking law in maintaining its existence in the face of the plague that is hitting Indonesia. OJK (Financial Services Authority) has also made a number of policies that are used as an effort to save the economy in Indonesia. One of the regulations is stated in POJK  Number 18 / POJK.03 / 2020 concerning "Written Orders for Handling Bank Problems". The legal policy used by Islamic banking is to measure the new OJK regulations as the organizer of an integrated regulatory and supervisory system of all activities in the financial services sector. The method used in this research is descriptive qualitative. The method used in this research is descriptive qualitative. related to the world of banking. The method used in this research is descriptive qualitative. The object of this research is Islamic banking which has more religious wisdom. The results of this study indicate that Islamic banking is making service updates, considering that the transition of the banking world to digital can increase the efficiency of work processes and improve the quality of customer service, by digitizing during the pandemic. The bank has made long-term investments and it is projected that digital services will be one of the main drivers of sustainable banking industry growth in the context of fulfilling POJK Number 18 / POJK.03 / 2020.